CHILDREN LITERATURE AND SOME DOCKET ABOUT IT UZBEKISTAN STATE WORLD LANGUAGE UNIVERSITY - Dilfuza Rasulmukhamedova; Tikayev Guseyn Gadjiibragimovich (Western European Studies, 2024)
In this article entitled сhildren literature and some of its issues, the science of children's literature and its teaching, problems and difficult situations, current issues facing the science are discussed. At the same time, there will be brief thoughts and opinions about how to replace today's y
Keywords: Turkish Gulistan and ethics; Uzbek children literature; Mahbub-ul Kulub